Exploring consumers' attitudes towards paper products that could be derived from transgenic plantations in Greece. (1st January 2015) - Tsourgiannis, Lambros; Kazana, Vassiliki; Karasavvoglou, Anastasios; Tsourgiannis, Christos Antonios; Florou, Giannoula; Polychronidou, Persefoni
This paper aims at exploring consumers' purchasing behaviour towards paper products that could be derived from transgenic plantations. Field interviews were conducted to a randomly selected sample of 205 consumers, who declared that they would buy such paper products. Principal Components Analysis indicated that the main factors affecting consumers' purchasing behaviour towards those products are potential environmental impacts of biotechnology use in forest trees, marketing issues relevant to paper products and product characteristics. Moreover, potential environmental and economic impacts mainly influence consumers' attitudes towards biotechnology use in forest trees. Through cluster techniques three groups of consumers with similar consumption behaviour were identified: a) opportunists; b) consumers with environmental concerns about biotechnology use; c) consumers interested in marketing issues. Discriminant analysis was performed to predict cluster membership and a non–parametric test to profile each consumer group according to personal characteristics and attitude towards biotechnology use in forest trees.